1996
DOI: 10.1007/bf02333424
|View full text |Cite
|
Sign up to set email alerts
|

Psychological abuse of women: Six distinct clusters

Abstract: This study was designed to identify patterns of psychological abuse (abuse) and determine whether different patterns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 52 publications
3
70
0
4
Order By: Relevance
“…Yet, perception of social support from friends (rather than parents) was related to lower bulimic propensities. The reasons for this differential pattern of results are uncertain, but the reasons may be linked to the often ambiguous nature of psychological aggression (Marshall, 1996), such that women may be more likely to turn inward to contend with their distress (Coffey, Leitenberg, Henning, Bennett, & Jankowski, 1996;Katz et al, 1997). In this instance, friends may not serve a direct supportive function vis a vis the abuse, but rather may provide a basis for active distraction or disengagement from the stressful situation and thus, attenuate the severity of the symptomatic bulimic behaviors that women adopt.…”
Section: Discussionmentioning
confidence: 85%
“…Yet, perception of social support from friends (rather than parents) was related to lower bulimic propensities. The reasons for this differential pattern of results are uncertain, but the reasons may be linked to the often ambiguous nature of psychological aggression (Marshall, 1996), such that women may be more likely to turn inward to contend with their distress (Coffey, Leitenberg, Henning, Bennett, & Jankowski, 1996;Katz et al, 1997). In this instance, friends may not serve a direct supportive function vis a vis the abuse, but rather may provide a basis for active distraction or disengagement from the stressful situation and thus, attenuate the severity of the symptomatic bulimic behaviors that women adopt.…”
Section: Discussionmentioning
confidence: 85%
“…This distinction theoretically contextualizes aggression in community samples (typically situational couple violence) in relation to more traditional notions of domestic violence (i.e., intimate terrorism), and underscores the importance of examining both husband and wife aggression. This study will also examine emotional or psychological aggression, which some women have reported being even more upsetting than physical abuse they have experienced (Follingstad, et al, 1990), which causes harm, even in the absence of physical aggression (Marshal, 1996;Pico-Alfonso et al, 2006;Taft et al, 2006), and which victims have identified as a primary variable in the assessment of their safety (Cattaneo, 2007). Although most research on emotional aggression has focused on female victims, consistent gender differences have not been found (Coker, et al, 2002;Hamby & Sugarman, 1999;Hines & Saudino, 2003;Swan & Snow, 2002).…”
mentioning
confidence: 99%
“…Therefore, the purpose of this study was to examine several potential correlates of engagement and disengagement coping. Although no published study has comprehensively examined the correlates of the coping variables of interest among battered women, some work within the general coping and domestic violence literatures suggest the potential importance of (a) abuse-related factors, (b) socioeconomic and social coping resources, and (c) childhood trauma (Holahan & Moos, 1987;Mitchell & Hodson, 1986;Waldrop & Resick, 2004).There is evidence from samples of battered women that higher levels of abuse are positively associated with the use of both engagement Jacobson, Gottman, Gortner, Berns, & Shortt, 1996;Marshall, 1996;Strube, 1988) and disengagement (Mitchell & Hodson, 1983) forms of coping. However, validated measures of these forms of coping have rarely been used, and few studies have assessed the impacts of psychological aggression or intimate partner sexual aggression in addition to physical assault.…”
mentioning
confidence: 99%